Clinical, microbiological, and biomarker profiles of mechanically ventilated icu patients with positive tracheal aspirate cultures - Filiz Çimen; Ayhanım Tümtürk; Akif Burak Çakmak (Eurasian Journal of Anesthesiology and Intensive Care, 2026)
Aims: To evaluate antimicrobial resistance patterns, clinical characteristics, and inflammatory biomarker profiles in mechanically ventilated intensive care unit patients with positive tracheal aspirate cultures. Methods: Between January 2020 and December 2024, 187 intubated intensive care unit patients with positive tracheal aspirate cultures and complete biomarker data were retrospectively analyzed. Demographic characteristics, antimicrobial resistance patterns, clinical and microbiological findings, and exploratory biomarker profiles were recorded. Exploratory receiver operating characteristic analyses were performed to descriptively assess potential relationships between selected biomarkers and in-hospital mortality. Results: Gram-negative pathogens predominated (89.3%), and overall in-hospital mortality was 95.7%. Mortality was higher among patients with Gram-negative microorganisms than among those with Gram-positive microorganisms (97.0% vs. 83.3%, p=0.007) and increased progressively across resistance categories. APACHE II scores did not differ significantly between groups. Among the evaluated biomarkers, the Prognostic Nutritional Index, lactate, and the C-reactive protein-to-albumin ratio demonstrated moderate-to-high discriminatory performance and were associated with in-hospital mortality in exploratory receiver operating characteristic analyses. Conclusion: Gram-negative microorganisms and antimicrobial resistance were more frequently observed among patients with adverse outcomes in this high-risk intensive care unit cohort. Biomarker findings should be interpreted as exploratory observations requiring validation in prospective studies.